Inactivation of Escherichia coli O157: H7 in foods by emerging technologies: a review. (13th December 2022) - Kim, Han-Jung; Song, Won-Jae
Abstract: Escherichia coli O157: H7 is a representative foodborne pathogen that causes haemorrhagic colitis, bloody diarrhea, and fatal haemolytic uraemic syndrome. Previously, only conventional heat treatment was used to pasteurised food; however, this method decreases food quality, including colour change, denatures proteins, and causes lipid oxidation. Therefore, emerging technologies to inactivate pathogens in food that affect food quality minimally have been researched and developed. This review aims to compile research since 2018 and briefly describe the inactivation mechanisms of emerging technologies such as microwave, radio frequency, ohmic heating, superheated steam, ionising radiation (gamma irradiation, electron beam, and X-rays), high pressure, ultraviolet light, pulsed light, ultrasound, gas treatment, plasma, and combination treatments. Pulsed electric field and electrolysed water were excluded because few research papers were published after 2018. In addition, the shortcomings of emerging technologies in the control of E. coli O157: H7 and the directions for emerging technology research are presented. Taking advantage of emerging technologies with many benefits will significantly improve food safety.